The impact of Brexit uncertainties on international trade: Evidence from Belgium - Emerson Schmitz (National Bank of Belgium, 2019)
This paper investigates the short-run effects of the uncertainties brought along with the Brexit referendum on the bilateral trade between Belgium and its main trading partners. I find that import and export markets have specific dynamics and react differently to changes in political uncertainty and economic variables. While import flows are more rigid and do not react to the uncertainties related to the Brexit referendum, export flows are more sensitive to this event. Consequently, I find that the instable environment created by the Brexit referendum leads to lower intensive margin of Belgian exports to the UK in comparison to Belgium's' main neighboring countries. The impact of uncertainties is more pronounced in larger Belgian exporting firms in the period preceding the Brexit referendum, since these firms are better able to absorb the associated costs of postponing or diverting exports. The results for Belgian manufacturing firms, which are more responsive to changes in competitiveness, also suggest more intense reaction to the Brexit uncertainties than commodities' producers but are not conclusive.
Keywords: F13; F14; F15; F31; F60; 330; Brexit; European Union; political uncertainty; international trade; exchange rates